The Influence of Application Education for Sustainable Development (ESD) Material in Civic Education on Improving Students` Civic Disposition - Anggraini, Diana Noor; Sopianingsih, Pitria; Lukman, Eva Precilia (International Journal Pedagogy of Social Studies, 2020)
The concept and paradigm of sustainable development (sustainable development) then began to get attention by all groups, both at the national and global levels. Citizenship Education has a full contribution as a way of sustainable development by involving the participation of citizens in it. To this end, civic education must functionally convey fresh (knowledge civic knowledge), develop existing talents and convey useful skills (civic skills). This study aims to determine the effect of implementing Education for Sustainable Development materials in Civic Education teaching materials on improving students' civic disposition. This research approach uses a quantitative approach with a quasi-experimental method. The findings of this study are: 1) There is a significant difference in the increase in civic disposition between the control class of 0.637 and the experimental class of 2.635; 2) There is a positive and significant influence between the application of the Education for Sustainable Development material by 48.6% on the improvement of students' civic disposition, and 3) There is a positive student response to the Education for Sustainable Development material in Civic Education learning.